Aging‐like skin changes in metabolic syndrome model mice are mediated by mineralocorticoid receptor signaling. Issue 1 (16th November 2012) - Nagase, Takashi; Akase, Tomoko; Sanada, Hiromi; Minematsu, Takeo; Ibuki, Ai; Huang, Lijuan; Asada, Mayumi; Yoshimura, Kotaro; Nagase, Miki; Shimada, Tsutomu; Aburada, Masaki; Nakagami, Gojiro; et al.
Summary: Aging is accelerated, at least in part, by pathological condition such as metabolic syndrome (MetS), and various molecular pathways such as oxidative stress are common mediators of aging and MetS. We previously developed the aging‐like skin model by single ultraviolet (UV) irradiation on the MetS model mice. Recent studies revealed that mineralocorticoid receptor (MR) signaling plays a pivotal role for various tissue inflammation and damages in MetS. Although previous studies reported that MR is expressed in the skin and that overexpression of MR in the skin resulted in the skin atrophy, the physiological or pathological functions of MR in the skin are not fully elucidated. Here, we show the involvement of MR signaling in the aging‐like skin changes in our own model. Elevations of oxidative stress and inflammation markers were observed in the MetS mice, and the UV‐evoked aging‐like skin damages were attenuated by topical antioxidant. MR expression was higher in the MetS mouse skin, and notably, expression of its effecter gene Sgk1 was significantly upregulated in the aging‐like skin in the UV‐irradiated MetS mice. Furthermore, topical application of MR antagonist spironolactone suppressed Sgk1 expression, oxidative stress, inflammation, and the aging‐like changes in the skin. The 2‐week UV onto the non‐MetS mice, the more usual photoaging model, resulted in the skin damages mostly equivalent to the MetS mice with single UV, but they were not associated with upregulation of MR signaling. Our studies suggested an unexpected role of MR signaling in the skin aging in MetS status.